Co‐producing a board game to learn and engage about dementia inequalities: First impacts on knowledge in the general population - Clarissa Giebel; Kerry Hanna; Hilary Tetlow; Mark Gabbay; Jacqui Cannon (Health Expectations)
Abstract Background Receiving and accessing care after a diagnosis of dementia, both for the person and their carer, are fraught with inequalities. The aim of this public engagement activity was to co‐produce a board game about dementia inequalities to facilitate learning, dialogue and educate about different barriers, and facilitators, to diagnosis and care and to test the game's impact on dementia knowledge with the general public. Methods Two virtual and two face‐to‐face workshops with people with dementia, unpaid carers, health and social care professionals and Third Sector representatives were held between October 2022 and June 2023. Virtual workshops involved discussions of inequalities and how a board game may feature inequalities. The first face‐to‐face workshop was split into the same activities, aided by outcomes from workshops 1 and 2. Workshop 4 attendees tested the prototype. The impact of the game on knowledge about dementia and inequalities was tested at a game play workshop in October 2023. Results Forty stakeholders attended four workshops. Workshops provided step‐by‐step thoughts on how the game could be designed or modified. The final game, prototype tested in workshop 4, consists of a one‐sided, two‐half board depicting the prediagnosis process (left half) and postdiagnosis process (right half). Fifty‐two members of the general public participated in the game play workshop, which led to significant improvements in knowledge about dementia (p < .001) and inequalities (p < .001). Discussion The game can be used to improve knowledge about dementia inequalities for health and social care professionals, carers, people living with dementia, decision makers and the general public. Patient or Public Contribution This engagement activity fully involved people with dementia, unpaid carers, health and social care professionals and Third Sector representatives throughout, with two unpaid carers as public advisers on the team.